Perempuan dan Spiritualisme: Meredefinisi Image Jeanne D'Arc Dalam Roman Historis Barat - Udasmoro, Wening (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
Jeanne d'Arc has been the wellknown female hero in the Westem tradition. However, the opinion about this hero has varied according to how people interprete her existence. She was known using God's voice in order to convince the French army in defeating British troops. Some of the interpreters have argued that she used that voice to manipulate French troops in order to get her own glory. Others have argued that she was a real hero that passed over the French men's heroism. This article attempts to explore this female heroism from spiritual point of view. It is argued that the spiritual approach used by Jeanne d'Arc was not a manipulation but a strategy to negotiate power mostly handled by men in the arena of conflict.